The phylogenetic, pathogenicity and transmission capacity analysis of one H9N2 strain - Meng, LiJia; Tang, XinHao; Gu, WenYuan; Zhang, Cheng; Dong, Shishan (Frontiers in Veterinary Science, 2025)
Avian influenza is an acute and highly contagious infectious disease that can infect multiple hosts. The low pathogenic avian influenza virus (LP-AIV), represented by the H9-subtype can cause a decrease in egg production and immunosuppression, lead to respiratory diseases and other diseases, reduce poultry production efficiency, and seriously affect the sustainable development of the poultry industry. In this study, one strain of H9-subtype AIV was isolated, purified, and named A/Hebei/723/2019 (H9N2). Phylogenetic analysis indicated that the HA, NA and M genes of the isolated strain belonged to the Y280-like lineage in the Eurasian lineage. The PA, NP and NS genes belong to the SH/F/98-like lineage. The PB1 gene belongs to the Y439-like lineage. The PB2 gene belongs to the G1-like lineage. Moreover, this strain binds exclusively to the α-2,6 sialic acid receptor, exhibits low pathogenicity to mice, and can be transmitted directly through contact and aerosol transmission among guinea pigs. It has a potential risk of infecting mammals and provides reference value for the subsequent formulation of measures for disease prevention and control.